Pengujian Usabilitas Pada Penggunaan Platform Scratch - Zakia Access Asmaul Khusna; Yovi Litanianda (Repeater : Publikasi Teknik Informatika dan Jaringan, 2024)
This research tests the usability of the platform on new students of Informatics Engineering. Usability of is measured through three main variables: effectiveness, efficiency, and user satisfaction. Data was collected through pre-test and post-test involving 20 respondents using questionnaires and practical tasks. 20 respondents using questionnaires and practical tasks. The results of the study showed that the effectiveness and efficiency of the Scratch platform increased significantly from the pre-test to the post-test, reaching a level of effectiveness and efficiency, showing that the time required to complete programming tasks is reduced once users are familiar with the platform. User satisfaction also increased, with the majority of respondents feeling more comfortable and interested in using Scratch after testing. This research concludes that the Scratch platform is effective and efficient as a programming learning tool for new Informatics Engineering students.